2011
DOI: 10.1109/tce.2011.6018874
|View full text |Cite
|
Sign up to set email alerts
|

Computation-scalable algorithm for scalable video coding

Abstract: This paper presents a strategy that efficiently allocates the limited resource and still maintains the coding performance for the spatial scalability of H.264/SVC. An integrated computation-scalable algorithm is proposed on the basis of priority-based mode decision (PBMD) and activitybased motion estimation (ABME). The rate-distortion cost (RD-cost) of base layer is utilized as the priority to decide the mode in the enhancement layer, and the motion vector difference (MVD) in the base layer is employed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Hamamoto (2011) states that the computational complexity is reduced based on the correlation between the current frame and reference frame with search range, this however, reduces the redundant search range and candidate modes were reduced results in PSNR loss. It is reported that mode decision and motion estimation (ME) modules take from 60 to 90% of the computational time in the enhancement layers to acquire the best rate distortion cost from all variable block modes (Wang, 2011). Recently, a number of efforts have been made to explore fast algorithms in inter-mode prediction and intra-mode prediction in H.264 / SVC video coding.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Hamamoto (2011) states that the computational complexity is reduced based on the correlation between the current frame and reference frame with search range, this however, reduces the redundant search range and candidate modes were reduced results in PSNR loss. It is reported that mode decision and motion estimation (ME) modules take from 60 to 90% of the computational time in the enhancement layers to acquire the best rate distortion cost from all variable block modes (Wang, 2011). Recently, a number of efforts have been made to explore fast algorithms in inter-mode prediction and intra-mode prediction in H.264 / SVC video coding.…”
Section: Background and Related Workmentioning
confidence: 99%
“…As mentioned in [4], Wang et al analyze RD-cost correlation between BL and EL, and find out that it can efficiently decide the mode priority of EL by using the RDcosts of each sub-MB BL . Eq.…”
Section: Mode Priority Decision By Base Layermentioning
confidence: 99%
“…Because Mode SKIP has the lowest complexity in all inter modes, [3] uses the coding information of the co-located MB in BL and the neighboring MBs of the EL to predict the SKIP mode. Wang et al's method [4] is based on the priority-based mode decision (PBMD) and uses the RD-cost correlation between BL and EL to decide the mode priority in EL. In [5], the algorithm employs the correlation between BL and EL to predict the best mode of the EL and uses motion vector difference (MVD)of the BL to decide the search range of the EL to accelerate the encoding time.…”
Section: Introductionmentioning
confidence: 99%
“…In the SVC scenario, the video signal is split into several layers, and a receiver may decode a part of the bitstream due to its resource constraint. [1][2][3] Intra-prediction is an efficient method to reduce spatial redundancy in coded video data. 4 Both H.264/AVC and SVC adopt the line-by-line intra-prediction scheme.…”
Section: Introductionmentioning
confidence: 99%